2019
DOI: 10.1101/811174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple ribonuclease A family members cleave transfer RNAs in response to stress

Abstract: During stress, changes in gene expression are critical for cell survival. Stress-induced tRNA cleavage has been implicated in various cellular processes, where tRNA fragments play diverse regulatory roles. Angiogenin (ANG), a member of the RNase A superfamily, induces cleavage of tRNAs resulting in the formation of tRNA-derived stress-induced RNAs (tiRNAs) that contribute to translational reprogramming aiming at cell survival. The role of other stress-induced RNases in tRNA cleavage is poorly understood. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…For simplicity, we will call these fragments long tRNA halves (L-tRNAh) and short tRNA halves (S-tRNAh), respectively. Both species are detectable inside U2-OS cells stressed with sodium arsenite but L-tRNAh are produced at much higher levels 51 . In contrast, only the S-tRNAh are predicted to form RNase-resistant homodimers according to our previous studies 36 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For simplicity, we will call these fragments long tRNA halves (L-tRNAh) and short tRNA halves (S-tRNAh), respectively. Both species are detectable inside U2-OS cells stressed with sodium arsenite but L-tRNAh are produced at much higher levels 51 . In contrast, only the S-tRNAh are predicted to form RNase-resistant homodimers according to our previous studies 36 .…”
Section: Resultsmentioning
confidence: 94%
“…By analogy, we are tempted to speculate that secreted RNases such as ANG could play a role in extracellular RNA metabolism, preventing the toxicity associated with its intracellular activity in nonstressed cells 83 . Although the function of ANG in tRNA cleavage seems to be partially redundant 51,52 , its implications in extracellular RNA cleavage under physiological conditions remains to be elucidated. Redundancy might be lower in serum-free environments as the nervous system, where several mutations in ANG have been functionally linked to neurodegenerative diseases 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, RNase 1-dependent cleavage of the CCA tail occurs between the two cytidine residues of the CCA tail, whereas angiogenin cleaves between the second cytidine and the adenosine, probably due to the substrate preference of this enzyme ( 71 ). Several recent studies claim that tRNA halves are produced in cells even in the absence of angiogenin ( 72 , 73 ), or that cleavage of tRNAs at both anticodon loop and CCA tail is performed in the absence of angiogenin ( 74 ). Further work is needed to establish whether RNase 1 is involved in formation of intracellular tRNA halves in response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…While Ang-independent cleavage was reported in vitro and ex vivo 15,16 , it is unclear whether this process occurs in vivo . It is also unclear what enzymes or factors impact Ang-independent tRNA cleavage, what are the sites of this Ang-independent cleavage and how this process is related to cellular stress response.…”
Section: Introductionmentioning
confidence: 97%
“…tiRNAs are currently under the scope to be used as biomarkers for diseases such as stroke and malignancies 911 , nonetheless, the process of tRNA cleavage is not well understood in terms of regulation and exact function 6 . Canonically, tRNAs are cleaved by Angiogenin (Ang) at the anti-codon site to generate tRNA halves (tiRNAs) 12,13 , however, recent studies have identified Ang-independent cleavage 1416 . In addition, we observed in our previous report the existence of larger 5’tiRNA fragments implying cleavage away from the anti-codon site (i.e.…”
Section: Introductionmentioning
confidence: 99%